Réponses

2012-12-01T19:15:29+01:00

Bonjour,


1)


f(x)=g(x)


f(x)-g(x)=0


(3x -11)/ 7 - (-5x +2) /4 = 0

 

4(3x -11)/ 28 - 7(-5x +2) /28 = 0

 

(4(3x -11) - 7(-5x +2) )/28 = 0

 

(12x -44 +35x -14) )/28 = 0

 

(47x -58 )/28 = 0

 

47x -58 = 0

 

47x = 58

 

x = 58/47

 

 

2)

 

f(x)<g(x)

 

f(x)-g(x)<0

 

47x -58 < 0

 

x < 58/47

 

J'espère que tu as compris

A+

 

 

 

2012-12-01T19:26:16+01:00

Bonsoir

f(x) =g(x) 

(3x-11)/7 = (-5x+2)/4

4(3x-11)=7(-5x+2)

12x-44=-35x+14

35x+12x =14+44

47x =58

x =58/47 

pour f(x) < g(x)      x < 58/47